Strategi Peningkatan Karakter Siswa Melalui Program Taqwa Character Building di SD Darul Hikam Bandung - Eka Fitriyana Sari; Naila Alfa Khusna; Bibit Muzdalifah; Khoiril Hidayah; Elya Umi Hanik (Jurnal Riset Madrasah Ibtidaiyah, 2022)
The crisis of personality or character can indirectly affect the personality and behavior of adolescents in life. A number of student deviant behaviors such as skipping school, stealing, lying, brawls between students, drugs, and lack of manners are considered failures in character education. This study aims to determine the strategy of improving student character through the Taqwa Character Building program at SD Darul Hikam Bandung. The method used in this research is descriptive qualitative. In this study, data were collected through direct observation and documentation as well as written reference sources such as journals, theses, and the official blog of SD Darul Hikam Bandung. The findings of this study indicate that the strategy for improving the character of students through the Taqwa Character Building program at the Darul Hikam Elementary School in Bandung is running well and effectively. Internal strategies, in the school environment, are implemented through classroom learning, habituation activities, a school culture that familiarizes with 5S: smile, greeting, greeting, courtesy, and also the existence of a TCB camp program which is a supporter of improving student character. While the external strategy, with the teacher involving parents of students to work together in strengthening the formation of student character.